Humor in Psychiatry: Lessons From Neuroscience, Psychopathology, and Treatment Research - Berger, Philipp; Bitsch, Florian; Falkenberg, Irina (Frontiers in Psychiatry, 2021)
Humor is a ubiquitous human characteristic that is socially motivated at its core and has a broad range of significant positive effects on emotional well-being and interpersonal relationships. Simultaneously, however, impairments in humor abilities have often been described in close association with the occurrence and course of neuropsychiatric disorders, such as schizophrenia, social anxiety, or depression. In the past decade, research in the neuroimaging and psychiatric domain has substantially progressed to i) characterize impaired humor as an element of psychopathology, and ii) shed light on the neurobiological mechanisms underlying the role of humor in neuropsychiatric diseases. However, iii) targeted interventions using concepts of positive psychology have revealed first evidence that a systematic training and/or a potential reactivation of humor-related skills can improve rehabilitative outcome in neuropsychiatric patient groups. Here, we sought to integrate evidence from neuroscience, as well as from psychopathology and treatment research to shed more light on the role of humor in psychiatry. Based on these considerations, we provide directions for future research and application in mental health services, focusing on the question of how our scientific understanding of humor can provide the basis for psychological interventions that foster positive attitudes and well-being.